Predictive value of ACEF score for acute kidney injury after surgical aortic valve replacement - Demirci, Gökhan; Demir, Ali Rıza; Kahraman, Serkan; Çamcı, Sencer; Yılmaz, Emre (The European Research Journal, 2024)
Objectives: Aortic stenosis is the most common form of degenerative heart valve disease. Acute kidney injury (AKI) after aortic valve replacement (AVR) is a common complication and is related to worse outcomes. Age, creatinine, and ejection fraction (ACEF) score is a simple scoring method that includes three parameters. Our study aimed to evaluate whether ACEF score could predict the development of AKI in patients who underwent AVR. Methods: A total of 366 consecutive patients who underwent isolated AVR for symptomatic severe aortic stenosis were evaluated retrospectively. The development of AKI was the primary endpoint of the study. The ACEF score was calculated by the formula: age (years)/left ventricular ejection fraction (%) + 1 (if baseline serum creatinine was >2 mg/dL). According to the ACEF score the study population was divided into two groups. Results: AKI was developed in 66 (18%) patients. The cut-off value of the ACEF score for the prediction of AKI was 1.07 with a sensitivity of 69.7% and a specificity of 56.7% (AUC 0.663; 95% CI: 0.589-0.736; P<0.001). AKI incidence was found to be higher in patients with high ACEF score than low ACEF score [46 (26.1%) vs. 20 (10.5%); P<0.001]. In addition, ACEF score [OR: 2.599; 95% CI: 1.399-4.828; P=0.002] and hemoglobin levels (OR: 0.837; 95% CI: 0.729-0.961; P=0.012) were found to be independent predictors of AKI. Conclusions: Our study revealed that the ACEF score is an independent predictor of AKI. ACEF score, as a simple and objective score, can be useful in predicting AKI in patients undergoing AVR.